TIPE ARGUMEN WACANA ARGUMENTASI TULIS SISWA SEKOLAH DASAR KELAS TINGGI - Ahmad Ridhani (LITERA, 2013)
This study aims to describe the types of arguments in written discourse by elementary school students. The data sources were writing by elementary school students in the upper grades in Sungai Kunjang Samarinda. The data were analyzed using a communication content analysis model. The findings show that there are three types of arguments, i.e. opinion, proof, and conclusion. The opinion argument is based on facts, interpretation,and evaluation. The proving argument is based on an observation of an object and general knowledge. The concluding argument is inductively and deductively made. The use of opinion, proof, and conclusion as arguments in written discourse is related to the preliminary knowledge stored in every person’s long-term memory.